TANAMAN TALAS AIR (Colocasia Esculenta (L.) Schott var. aquatilis Hassk) SEBAGAI AGEN FITOREMEDIASI PADA AIR LIMBAH SELOKAN - Putri Situmorang, Erika; Maya Citra Saragih, Dara; Wahyu Ananda, Luthfi; Ridho Shirfa Hana, Muhammad; Nilan Sari, Marlinda; Febryossa, Adelia (Universitas Cokroaminoto Palopo, 2024)
The aims of this research was to the determine the effectiveness of the taro plant (Colocasia esculenta (L.) Schott var. aquatilis Hassk) as a phytoremediation agent in treating domestic wastewater. Wastewater taken from the sewer in Williem Iskandar, Percut Sei Tuan District was analyzed using parameters such as pH, TDS, temperature and turbidity. The method used is constructed wetland, by placing taro plants in containers filled with sewer water in volumes (2.5 L, 5L, 7.5L and 10 L). Observations were carried out every other day for 6 days. The research results showed that after phytoremediation, the water quality experienced changes, indicating that the taro plant was effective in absorbing pollutants and improving water quality.